Designing Online Platforms for Customized Goods and Services: A Market Frictions–Based Perspective - Chu, Leon Yang; Wu, Brian (Academy of Management Review, 2023)
Through digitalization, online platforms facilitate suppliers to meet market demand with customized offerings, but this business model’s value-creation potential is often hampered by market frictio...